Volatile organic compounds involved in the communication of microalgae-bacterial association extracted through Headspace-Solid phase microextraction and confirmed using gas chromatography-mass spectrophotometry. (March 2022) - Chegukrishnamurthi, Madhubalaji; Shekh, Ajam; Ravi, Sarada; Narayana Mudliar, Sandeep
Graphical abstract: Highlights: First study to determine volatile organic compounds of Chlorella. Direct and indirect interactions of Chlorella with bacteria analysed. Industrially potential VOCs detected in Chlorella- bacterial communications. Abstract: In the present study, bacterial mixture ( Rhizobium and Agrobacterium ) and axenic Chlorella were cultivated individually, in a mixed (co-cultured) form, and through headspace connections to study volatile organic compounds (VOCs) profile and their effect on growth. Results indicated that VOCs produced by the axenic microalgae and microalgae co-cultured with bacteria were significantly different. Axenic Chlorella predominantly produced a flavouring organic compound 2-pentadecanone (69.54%), bacterial mixed culture produced 1-decanone, 1, 2, 3-butanetriol, and quinoline (15–20%), and direct co-culturing of Chlorella with bacteria predominantly produced 2-pentadecanone (32.4 %). When they were allowed to communicate distantly through headspace connection, highly diversified VOCs in large numbers but low quantities were noted, predominantly 1, 2-propanediol (28.82 %). In addition, growth of the co-cultured Chlorella was 1.5 times higher, while Chlorella in headspace connection with bacterial mixture exhibited ∼ 3.2 times increase in growth compared to the axenic Chlorella, indicating the essential role of VOCs in growth and communication.